Glaciological studies of the Institute of Geography of the Russian Academy of Sciences on Elbrus in 2024 - P. A. Toropov; I. I. Lavrentiev; A. Yu. Artamonov; E. D. Drozdov; T. D. Kiseleva; A. A. Abramov; I. M. Sushintsev; A. I. Degtyarev; A. G. Khairedinova; N. E. Elagina (Лëд и снег)
.